2012
DOI: 10.1095/biolreprod.112.101014
|View full text |Cite
|
Sign up to set email alerts
|

Aurora Kinase A Drives MTOC Biogenesis but Does Not Trigger Resumption of Meiosis in Mouse Oocytes Matured In Vivo1

Abstract: Aurora kinase A (AURKA) is an important mitotic kinase involved in the G2/M transition, centrosome maturation and separation, and spindle formation in somatic cells. We used transgenic models that specifically overexpress in mouse oocytes either wild-type (WT-AURKA) or a catalytically inactive (kinase-dead) (KD-AURKA) AURKA to gain new insights regarding the role of AURKA during oocyte maturation. AURKA activation occurs shortly after hCG administration that initiates maturation in vivo. Although AURKA activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 66 publications
5
37
0
Order By: Relevance
“…Additionally, it has been reported that Aurka is a critical regulator of spindle assembly and MTOC biogenesis in mouse oocytes. 25,27,38,39 Aurka localized in the cytoplasm of GV oocytes and accumulated on the spindle poles in MI and MII oocytes; another report had similar findings (Fig. S1C).…”
Section: Bcl2l10 Controls Meiotic Spindle Assembly By Regulating Mtocsupporting
confidence: 71%
See 1 more Smart Citation
“…Additionally, it has been reported that Aurka is a critical regulator of spindle assembly and MTOC biogenesis in mouse oocytes. 25,27,38,39 Aurka localized in the cytoplasm of GV oocytes and accumulated on the spindle poles in MI and MII oocytes; another report had similar findings (Fig. S1C).…”
Section: Bcl2l10 Controls Meiotic Spindle Assembly By Regulating Mtocsupporting
confidence: 71%
“…Because the auto-phosphorylation of Aurka occurred in the MTOCs of mouse oocytes, 25,27 we co-stained T288-Aurka and Pericentrin. T288-Aurka was not concentrated at the MTOC as indicated by Pericentrin but was dispersed in the cytoplasm of the MIarrested oocytes after Bcl2l10 RNAi (Fig.…”
Section: Bcl2l10 Rnai Disturbed Mtoc Formation In Oocytesmentioning
confidence: 99%
“…Because AURKA localizes to MTOCs (Saskova et al, 2008;Shuda et al, 2009;Solc et al, 2012), and because its inhibition can cause spindle pole instability in mitotic cells , we wondered whether haspin regulates AURKA localization at MTOCs. First, we compared AURKA levels in oocytes fixed at metaphase I by performing immunocytochemistry.…”
Section: Haspin Does Not Regulate Aurka Localization At Mtocsmentioning
confidence: 99%
“…One protein that localizes with the PCM in somatic cells and oocytes is Aurora kinase A (AURKA) (Saskova et al, 2008;Shuda et al, 2009;Solc et al, 2012). In somatic cells (Ma et al, 2011), upon binding a microtubule-binding protein called TPX2, AURKA auto-activates and regulates the building of the bipolar spindle by recruiting other PCM proteins, promoting microtubule nucleation and anti-parallel sliding forces, and maintaining the integrity of astral microtubules with the cortex (Dodson and Bayliss, 2012;Giubettini et al, 2011;Kufer et al, 2002;Li et al, 2008;Scrofani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation